The Construction of History and Nationalism in India : Textbooks, Controversies and Politics. - Guichard, Sylvie (Routledge Advances in South Asian Studies, 2010)
Most studies on nations and nationalism argue that history, or more precisely a 'common past', is crucial for the process of national identity building. This book focuses on the construction, elaboration and negotiation of the narratives that have become official history in India.